2014
DOI: 10.1016/j.ejar.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of elevated CO2 concentrations on the growth and ultrastructure of non-calcifying marine diatom (Chaetoceros gracilis F.Schütt)

Abstract: The impacts of different CO 2 concentrations on the growth, physiology and ultrastructure of noncalcifying microalga Chaetoceros gracilis F.Schu¨tt (Diatom) were studied. We incubated Ch. gracilis under different CO 2 concentrations, preindustrial and current ambient atmospheric concentrations (285 and 385 latm, respectively) or predicted year-2100 CO 2 levels (550, 750 and 1050 latm) in continuous culture conditions. The growth of Ch. gracilis measured as cell number was decreased by increasing the pCO 2 conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
1
8
0
2
Order By: Relevance
“…The effect of CO 2 on the growth of diatoms is quite complex and, probably, depends on the particular physiology of each species. It has been shown that species can use different carbon sources, with some utilizing CO 2 as main carbon source, whereas others mostly drawing carbon from HCO 3 - [35]. Elevated CO 2 concentration did not cause significant differences in growth in diatoms such as Asterionella glacialis , Thalassiosira punctigera , Coscinodiscus wailesii , Phaeodactylum tricornutum [3638].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of CO 2 on the growth of diatoms is quite complex and, probably, depends on the particular physiology of each species. It has been shown that species can use different carbon sources, with some utilizing CO 2 as main carbon source, whereas others mostly drawing carbon from HCO 3 - [35]. Elevated CO 2 concentration did not cause significant differences in growth in diatoms such as Asterionella glacialis , Thalassiosira punctigera , Coscinodiscus wailesii , Phaeodactylum tricornutum [3638].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated CO 2 concentration did not cause significant differences in growth in diatoms such as Asterionella glacialis , Thalassiosira punctigera , Coscinodiscus wailesii , Phaeodactylum tricornutum [3638]. In the case of Chaetoceros gracilis , the maximum number of cells was obtained at a carbon dioxide concentration of 385 μatm and a lower cell number was obtained at lower (control and 280 μatm) and higher levels of carbon dioxide (1,050 μatm) [35]. In other species, such as Thalassiosira weissflogii , algal density decreased with the decreasing pH [39] probably because, when the acidity is lower than a certain concentration, it will impair algal physiological functioning [40].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, low CO 2 level is insufficient for microalgal growth, whereas high CO 2 level often exerts detrimental effect (35; 36; 37). Chloroplast damage and organelles disorder which in turn render cell lysis were observed in high CO 2 level (38). Many microalgae have evolved CO 2 concentrating mechanism (CCM) to enhance the efficiency of photosynthetic carbon fixation by raising the CO 2 level around carboxylating enzyme ribulose bisphosphate carboxylase/oxygenase (RuBisCO) which responsible for the first step of carbon dioxide fixation ( Figure 2).…”
Section: Carbonmentioning
confidence: 99%
“…Hal tersebut terjadi karena pada konsentrasi 385 ppm CO 2 makroalga masih dapat melakukan proses fisiologi dengan baik karena kebutuhan akan kalsium karbonat masih normal, ketika terjadi kenaikan konsentrasi CO 2 maka terjadi disolusi karbonat yang berpengaruh terhadap lapisan utricle dalam thallus sehingga mengganggu proses fotosintesa dan respirasi apalagi dengan terjadinya peningkatan suhu maka kebutuhan komponen dan proses metabolik semakin bertambah sehingga kemampuan kloroplas dalam dinding sel semakin menurun pula (Dijoux et al, 2012). Hasil penelitian Khairy et al (2014) juga terjadi pada fitoplankton Chaetoceros gracilis mengalami kerusakan kloroplas, disintegrasi membran tilakoid, dan terjadinya sel lyses ketika terjadi peningkatan konsentrasi CO 2 550-1.050 ppm.…”
Section: Kandungan Klorofil-aunclassified
“…Selanjutnya penjelasan Barry (2011) bahwa konsekuensi dari tingginya konsentrasi CO 2 adalah menurunnya aktifitas enzim, terjadi inefisiensi fungsi seluler (seperti sintesa protein), terjadi depresi metabolik, bahkan pada organisme fitoplankton berpengaruh terhadap produksi pigmen sel 689 dan produktifitasnya. Selanjutnya hasil penelitian Khairy et al (2014) bahwa kandungan total protein, karbohidrat dan lipid pada fitoplankton Chaetoceros gracilis menurun pada konsentrasi 550-1.050 ppm CO 2 . Sejalan dengan penemuan Porzio et al (2013) bahwa ganggang laut menunjukkan respon yang berbeda terhadap pengasaman laut, yang mana pada penurunan pH tidak selalu mendukung organisme fotosintetik laut.…”
Section: Pembahasanunclassified